2020
DOI: 10.21203/rs.2.16764/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global analysis of CNVs in Chinese indigenous fine-wool sheep populations using whole-genome resequencing

Abstract: Background: Copy number variation (CNV) is an important source of genetic variation that has a significant influence on phenotypic diversity, important economic traits and the evolution of livestock species. In this study, the genome-wide CNV distribution characteristics of 32 fine-wool sheep from three breeds were analyzed using resequencing. Results: A total of 1747604 CNVs were detected in this study, and 7228 CNV regions (CNVR) were obtained after merging overlapping CNVs; these regions accounted for 2.17%… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…We measured the relative copy numbers of one deletion and all duplications using qPCR on the QuantStudio TM 6 Flex Real-Time PCR System (Life Technologies, Carlsbad, CA, USA) using SYBR Green kit (Promega, Madison, WI, USA). Following a previous study on sheep 95 , DGAT2 gene was used as the internal reference gene. qPCR reaction was in 25 μL volume consisting of 12.5 μL 2× SYBR Green qPCR Mix (Life Technologies, Carlsbad, CA, USA), 1 μL (10 pmol/µL) each primer (forward and reverse), 2 μL template DNA (30 ng/μL), and 8.5 μL ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…We measured the relative copy numbers of one deletion and all duplications using qPCR on the QuantStudio TM 6 Flex Real-Time PCR System (Life Technologies, Carlsbad, CA, USA) using SYBR Green kit (Promega, Madison, WI, USA). Following a previous study on sheep 95 , DGAT2 gene was used as the internal reference gene. qPCR reaction was in 25 μL volume consisting of 12.5 μL 2× SYBR Green qPCR Mix (Life Technologies, Carlsbad, CA, USA), 1 μL (10 pmol/µL) each primer (forward and reverse), 2 μL template DNA (30 ng/μL), and 8.5 μL ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were reported in other livestock species e.g., dairy cattle (182,823 CNVs) [ 70 ], yak (98,441 CNVs) [ 39 ], Nellore cattle (195,873 CNVs) [ 71 ], and goat (208,649 CNVs) [ 26 ]. Some other studies reported a wide range of CNVs from 12 CNVs in chicken [ 72 ] to 1,747,604 CNVs in sheep [ 23 ]. This discrepancy might be due to the differences in the sample size, algorithms used for CNV calling, and sequencing technology [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of Wnt signaling pathway is a critical part to hair-inducing activity of dermal papilla through regulating the β-catenin pathway, and thereby required for follicle regeneration and growth of the hair shaft [ 94 , 95 ]. Interestingly, Yuan et al [ 23 ] demonstrated the contribution of Wnt signaling pathway to the hair follicle development process in Alpine Merino sheep by identifying Wnt-related signaling pathways associated with CNVR-harboring genes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations